2017
DOI: 10.1097/inf.0000000000001383
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Gastric Microbiota in a Pediatric Population According to Helicobacter pylori Status

Abstract: We characterized the gastric microbiota for the first time in children with and without H. pylori and observed that when H. pylori is present, it tends to dominate the microbial community. In the H. pylori-negative patients, there was more relative abundance of gammaproteobacteria, betaproteobacteria, bacteroidia and clostridia classes and a higher bacterial richness and diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 28 publications
7
79
1
Order By: Relevance
“…It should be noted that even in some H pylori negative individuals (deemed H pylori negative by conventional methods), the bacterium can be detected when employing highly sensitive DNA‐based detection. In a paediatric cohort from Spain, 18 children were designated as H pylori positive while low abundance of H pylori was detected in another 17 children (on average 0.45% abundance within the gastric microbiota). Similarly, in a small‐scale sequencing study on a Chinese cohort, the microbiota of six H pylori positive and six H pylori negative patients was sequenced and revealed that five of six H pylori negative individuals were carriers (again in low abundance from 0.04% to 0.67%).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that even in some H pylori negative individuals (deemed H pylori negative by conventional methods), the bacterium can be detected when employing highly sensitive DNA‐based detection. In a paediatric cohort from Spain, 18 children were designated as H pylori positive while low abundance of H pylori was detected in another 17 children (on average 0.45% abundance within the gastric microbiota). Similarly, in a small‐scale sequencing study on a Chinese cohort, the microbiota of six H pylori positive and six H pylori negative patients was sequenced and revealed that five of six H pylori negative individuals were carriers (again in low abundance from 0.04% to 0.67%).…”
Section: Resultsmentioning
confidence: 99%
“…Liorca et al. aimed to compare the gastric microbiota in pediatric patients with (n=18) and without (n=33) H. pylori infection, who underwent gastric endoscopy for dyspeptic symptoms. Bacterial richness and diversity were lower in H. pylori‐ positive specimens than in those negative, and both groups were clearly separated according to beta diversity.…”
Section: Helicobacter Pylori and Gastric Microbiotamentioning
confidence: 99%
“…They reported higher microbial diversity and richness in H. pylori -negative subjects. [74] Several factors have been suggested that may account for shifts in the gastric microbiome with H. pylori infection: [1] increased gastric pH secondary to long-term H. pylori infection favors the colonization of transient bacteria, [2] ammonia and bicarbonate produced as a result of urease activity may be used as substrates for other bacteria, and [3] H. pylori -induced decreased gastric motility. [75]…”
Section: Gastric Microbiomementioning
confidence: 99%